Consumers awareness of white-striping as a chicken breast myopathy affects their purchasing decision and emotional responses. (September 2020) - de Carvalho, L.M.; Ventanas, S.; Olegario, L.S.; Madruga, M.S.; Estévez, M.
Abstract: The aim of this study was to evaluate consumers' degree of knowledge, acceptability, and purchase intention of chicken breasts affected by the white striping (WS) myopathy. The emotions evoked in consumers in two different consumption situations (before [BI] and after [AI] being informed of the WS condition) was also assessed. Raw WS samples presented lower acceptability and purchase intent than N counterparts. In the AI scenario, acceptability of WS samples significantly decreased while consumer's rejection increased found. One-fifth of consumers refused to eat WS meat after the report of myopathy. Upon cooking, consumers who decided to taste, detected no differences between WS and N chicken breasts for color, flavor and overall acceptability and the informed situation had a negligible impact. However, the WS samples had higher scores of acceptability for odor and texture parameters compared to the N counterparts. WS myopathy increases the emotions "interested" and "enthusiastic", although no major differences in the emotional profile were observed. The degree of knowledge about WS myopathy was inversely proportional to the consumer's acceptability and purchase intention of commercial fresh chicken breasts. Further studies are required to confirm this trend in a larger group of population as well as in other countries and cultures. Highlights: Consumers from this study were unaware of the white striping (WS) myopathy. Awareness of the myopathy penalized consumer acceptability and willingness to buy. High rejection of breasts with stretch marks, even under non-informed conditions. One-fifth of consumers refuse to eat WS meat after the report of myopathy. The myopathy awareness affects the consumer's emotional profile.